Menelusuri Metodologi Ekonomi Islam Abdel-Rahman Yousri Ahmed - Ahmad Ubaidillah (Universitas Islam Lamongan, 2017)
In recent years, we have witnessed a high interest in the study of methodology in the field of Islamic economics. Works in the form of books, journals, or articles on methodologies have developed rapidly over the past two decades. People’s interest binding up in Islamic economics in the field of methodology is caused by several factors, among which there are those who think that the economy is not going well. Poverty still exists. Unemployment is growing along with high inflation and hardly any reliable solution to the depression of the local economy, even the regional financial crisis. Another reason for the revival of interest in the field of economic methodology is that economists, in their efforts to instill a positivistic paradigm of natural science into economics, tend to break the science of philosophy that raises ethical and moral issues relating to human goals and behavior. This paper will attempt to answer the question: what is the Islamic economic methodology offered by Abdel-Rahman Yousri Ahmed and what should the Islamic economic exponents do in the formulation of Islamic economics theory? This type of research is qualitative with the approach of figure thinking. The data collection technique is done by reading the works of Abdel-Rahman Yousri Ahmed and some supporting writings of the research. The result of study shows that the commitment to make the theory of Islamic economics must be realized into the form of blend between Sharia rules and Islamic values into postulates or axioms. The resolving of various problems, the process of economic analysis, and the formulation of rules that explain Islamic economics, should be based on the postulates or the axioms. The empirical experience of Islamic economics is a mandatory requirement for formulating empirical theory. Islamic economics scientific theory consists of three main elements: definition or terminology, postulates (axioms or assumptions), and hypotheses. From an Islamic perspective, definitions and postulates which are composed and made in accordance with Islamic and Shari’a values, should be ensured to show the character of the Islamic hypothesis that culminates in the theoretical work. The historical experience of Islamic economics in the past will greatly help modern Islamic economics. The Islamic economics applicability depends heavily on using correct methodology in formulating theory. Keywords: Islamic Economics Methodology, Abdel-Rahman Yousri Ahmed